An apparatus for removing contaminants from palm kernel cake and a method thereof - Abdullah, Norhani; Roslan, Muhamad Akhmal Hakim; Abd. Shukor, Mohd. Yunus; Shakirin, Faridah Hanim (2014)
The invention relates primarily to an apparatus for removing contaminants such as kernel nutshells from palm kernel cake (PKC) in order to reduce lignin content of the PKC. The invention is relevant in field of animal feed production. The apparatus mainly comprises of a supporting means (2), a separator (4) having electrostatic conductivity and a vibrating device (8) engaged to the supporting means (2).